PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR, MOTIVASI DAN KINERJA (Survey Pada Karyawan Hotel Berbintang di Kota Malang dan Batu) - Warsito, Bambang (Jurnal Ekonomi Modernisasi, 2008)
This research seeks to investigate the relationship between organizational culture variables, work environment, organizational citizenship behavior, motivation and performance in the star-typed hotel industry at Malang and Batu. This research was purposed to assess the differences of organizational culture, work environment, organizational citizenship behavior, motivation and performance based on the characteristic of respondents. This research was categorized as survey one using cross-sectional study to 15 star-typed hotels at Batu and Malang. The result of investigation using SEM technique indicated that the model developed had moderate fit level. The result of Goodness of fit indices showed moderate result to all construct in the model. Partially, the construct developed showed good outcome in goodness of fit evaluation. Generally, all exogenous variables (organizational culture and work environment) significantly affected the performance of employee. Some hypotheses expected on this research were supported, and some of these were not supported. Organizational culture significantly affected organizational citizenship behavior and employee performance, but insignificantly affected motivation. Work environment significantly influenced organizational citizenship behavior but insignificantly affected motivation. Organizational citizenship behavior insignificantly affected motivation, but motivation significantly affected the employee performance.